If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3) * 2 = -3 + k Reorder the terms: (3 + x) * 2 = -3 + k Reorder the terms for easier multiplication: 2(3 + x) = -3 + k (3 * 2 + x * 2) = -3 + k (6 + 2x) = -3 + k Solving 6 + 2x = -3 + k Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2x = -3 + -6 + k Combine like terms: 6 + -6 = 0 0 + 2x = -3 + -6 + k 2x = -3 + -6 + k Combine like terms: -3 + -6 = -9 2x = -9 + k Divide each side by '2'. x = -4.5 + 0.5k Simplifying x = -4.5 + 0.5k
| (3u+2)(7+u)=0 | | 7(y+6)+7y=9 | | 29x^2-24x-1.44=0 | | 4(x+1.48)=3x | | 5w+3w=20 | | 3y-5=12 | | .3x^2-.7x-4.0=0 | | 15+3m=7m+3 | | -2.29x^2-.24x-.0144=0 | | 32x+17y=196 | | S-1.8x=6.4 | | x^2+12x+100=y | | -6(6x+2)=4x-12 | | (2x-1)(x+3)=15 | | -4(t+1)-t-14=-5(t+5)+7 | | 3x(6+x)=24 | | 16-y=9 | | -4x+18=-2x+10 | | 5(x+2)+3(2x-3)=34 | | (7n/n-3)-4=15/n-3 | | -21p-5(6-6p)=4(p-2)-22 | | m/3-m/5=6 | | .29x^2-.24x-.0144=0 | | -3x^2+2x+5=x | | log(3x-17)=6 | | (5+z)(4z+1)=0 | | -7(v+4)+3v+7=8v+6 | | 4x=11.4285 | | 60+6x=70+4x | | a+(a+15)=265 | | 3e^2+5e= | | 14(v+4)-2v=4(3v+2)-16 |